The impact of policies on development-induced resettlement processes and outcomes: a Lesotho-India comparative study - Tsietsi, Teboho Priscilla Mosuoe (Rhodes University, Faculty of Humanities, Department of Anthropology, 2019)
The practice of Development-Induced Displacement and Resettlement (DIDR), historically, has often led to negative consequences for those affected by development projects, including but not limited to, the construction of large dams. Although DIDR arises from the need to provide goods and services that characterise development, it often leaves those who are forced to give up their assets, resources, and long standing social networks in dire socio-economic conditions as a result of resettlement. In many such cases, the provision for losses suffered by those primarily affected is often insufficient, leading to further losses experienced as a result of the complete life change experienced by those affected by resettlement. Research has shown that the insufficiency of such provisions for losses is attributable to not only the value of the provision itself, but also the manner in which resettlement processes are implemented. While early on, researchers believed that the development of policies would have a significant, positive impact on the practice of resettlement and its outcomes, evidence would later show that the development of policies alone is not a panacea for all challenges associated with forced resettlement. Further research revealed that resettlement is characterised by inherent and active complexities which are often at play, and may impede effective implementation. Hence, while the development of policies is essential, both the development and implementation of policies must be undertaken in a manner that seeks to actively address the inherent complexities of resettlement. This thesis aims to explore the implementation of resettlement policies in two case studies, where in one case, resettlement was informed by national policy, and in the other, by policies developed by a parastatal tasked with the responsibility of executing resettlement. The study makes a comparative analysis between the two cases, and explores the factors at play in the implementation of resettlement policies "“ whether such factors serve to facilitate or impede effective implementation "“ as well as the nature of the outcomes on the ground. As an overarching goal, the research aims to provide a basis upon which a framework for the development of a national level policy of resettlement may be developed. In this regard, the thesis undertakes a comparison of the Indian resettlement case with the Lesotho case. The former, in addition to having developed a resettlement policy at the national level, has a long history of experience in forced resettlement and displacement, from which invaluable lessons have been learned. The latter, on the other hand, has no resettlement policy at the national level, although the country has also experienced forced resettlement dating back to nearly three decades ago. Although India and Lesotho have distinct social, cultural, economic and demographic characteristics, research has shown that the complexities of forced resettlement, and their outcomes on affected people, are largely applicable across the different contexts. Hence, certain dimensions and lessons can be transferable from the Indian case to the Lesotho case, and vice versa. However, for the purpose of this thesis, the focus is on providing a basis for national policy development in Lesotho, in light of Indian policies and practice. The empirical basis of the thesis is an ethnographic study undertaken in relation to the Chandil Dam resettlement case in Jharkhand, India and the Mohale Dam resettlement case in Maseru, Lesotho. The thesis engaged both qualitative and quantitative research methods, as well as four, complementary theoretical tools that analyse the effects of forced resettlement on affected people. The thesis reveals that the negative consequences of forced resettlement resulting from its inherent complexities continue to manifest with concerning effects on the lives of those affected. It shows that the implementation of policies is a complex process that requires collaborative effort from a wide range of stakeholders in a given context. National policies of resettlement are, thus, instrumental in this regard, as they can create an enabling environment for the facilitation of collaborative efforts towards sustainable livelihood re-establishment for those who involuntarily suffer losses to resettlement.
Keywords: Forced migration -- Lesotho; Forced migration -- India; Dams -- Social aspects -- Lesotho; Dams -- Social aspects -- India; Irrigation projects -- Economic aspects -- Lesotho; Irrigation projects -- Economic aspects -- India; Land settlement -- Government policy -- Lesotho; Land settlement -- Government policy -- India